Internet-Delivered Cognitive-Behavioral Therapy for Social Anxiety Disorder in Romania: A Randomized Controlled Trial - Tulbure, Bogdan Tudor; Szentagotai, Aurora; David, Oana; Ștefan, Simona; Månsson, Kristoffer N. T.; David, Daniel; Andersson, Gerhard (PLOS ONE, 2015)
Background and Aims Internet-based cognitive-behavioral therapy (iCBT) for social anxiety disorder has been found effective, as attested by independently conducted randomized controlled trials in four languages. The study aim is to test the efficacy of an iCBT program in a culture where it was not tested before (i.e. Romania). Methods Participants (n = 76) were recruited, screened and randomized to either a nine-week guided iCBT or a wait-list control group in April and May 2012. Self-report measures were collected before (April 2012) and after the intervention (July 2012), as well as six months later (January 2013). Although social anxiety was assessed with multiple measures, the Liebowitz Social Anxiety Scale - Self Report version (LSAS-SR) and Social Phobia Inventory (SPIN) were used as the primary outcome measures. Results A significant difference with a large between-group effect size in favor of iCBT was found (Cohen´s d = 1.19 for LSAS-SR and d = 1.27 for SPIN). Recovery rates show that 36.8% (n = 14) in the treatment group score below the SPIN clinical cut-off compared to only 2.6% (n = 1) in the wait-list control group. Post-intervention clinical interviews also revealed that 34.2% (n = 13) of the treatment group was completely recovered (full remission) while additionally 36.8% (n = 14) retained some social anxiety symptoms (partial remission). However, an important study limitation is that post-intervention interviewers were not blinded to the study conditions. The program also effectively reduced depression and dysfunctional thinking (between-group Cohen´s d = 0.84 for depression and d = 0.63 for dysfunctional thinking). Moreover, the iCBT intervention appears to have a long-term impact for participants’ functioning, as the treatment gains were maintained six months later. Conclusions Internet-delivered interventions display a high potential to quickly and widely disseminate effective evidence-based programs around the world. This study provides support for guided iCBT as a promising treatment approach in Romania. Trial Registration ClinicalTrials.gov NCT01557894